Biological activity of the essential oil of Drimys winteri - Navarro, Myriam; Urrejola, Felipe; Espinoza, Misael; Silva, Simón; González, Sebastián; Utreras, Diego; Fernandez, Katia; Bravo, Jessica (Frontiers in Chemistry, 2024)
Abbreviatures: Essential oil (EO), GC-MS (Gas chromatography-mass spectrometry), Drymis winteri (DW), 2,2'-Azobis 2-amidinopropane dihydrochloride (AAPH), Butylated hydroxytoluene (BHT), Half maximal inhibitory concentration (IC50), 2,2-difenil-1-picrilhidracilo (DPPH), Ferric Reducing Antioxidant Power (FRAP), Nuclear factor erythroid 2-related factor 2 (NRF2), Glutathione S-Transferase Pi 1(GSTP1), Superoxide dismutase 1(SOD1), NAD(P)H quinone oxidoreductase 1 (NQO1), Glutathione peroxidase 1 (GPX1), Heme Oxygenase-1 (HMOX), Catalase (CAT), Glutathione (GSH), Malondialdehyde (MDA), Nicotinamida adenina dinucleótido fosfato (NADPH), Superoxide dismutase (SOD), Tumor factor necrosis alfa (TNF-α), Interleukin-1β (IL-1β), Interleukin-6 (IL-6).